Improvements Evaluation of High-Speed Electro-Optical Integrated Thin-Film Microwave Coupler SOA-based Space Switch - Tiago Sutili; Rafael C. Figueiredo; Napoleão S. Ribeiro; Cristiano M. Gallep; Evandro Conforti (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract The speed and transient improvements due to a thin- film microwave coupler on a high-speed SOA-based space switch are analyzed. The switch performance is compared with another one using the same SOA device but in its commercial butterfly encapsulated form factor. Through an extensive experimental characterization and an automated algorithm analysis, the switching actions were evaluated in several SOA operational conditions (bias current, electrical pulse step amplitude, preimpulse amplitude, and switching technique) employing metrics related to the switching times and transient behavior intensity. The results showed that the thin-film coupler SOA switch mounting led to switching time improvements and quicker optical output pulse stabilization. In conjunction with the appropriated switching technique, the device could achieve switching speeds around 200 ps aiming its operation in high-speed optical networks.